2021
DOI: 10.1002/ajmg.a.62413
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of novel genetic variants of NKX2‐5 associated with nonsyndromic congenital heart disease

Abstract: NKX2-5, a master cardiac regulatory transcription factor was the first known genetic cause of congenital heart diseases (CHDs). To further investigate its role in CHD pathogenesis, we performed mutational screening of 285 CHD probands and 200 healthy controls. Five coding sequence variants were identified in six CHD cases (2.1%), including three in the N-terminal region (p.A61G, p.R95L, and p.E131K) and one each in homeodomain (HD) (p.A148E) and tyrosine-rich domain (p.P247A). Variant-p.A148E showed tertiary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 85 publications
(143 reference statements)
0
7
0
Order By: Relevance
“…NKX2-5 is a transcription factor previously demonstrated to have highly specific expression in heart tissue, which is in congruence with the fact that this gene belongs to the top quantile (40) within both our specificity quantile and mean expression quantile metrics. This gene was in fact the first known genetic risk factor for congenital heart disease, and its expression is necessary not only for the development of cardiomyocytes but also the continued functioning of heart cells into adulthood 32,33 .…”
Section: Exemplar Results Identify Known Associations While Revealing...mentioning
confidence: 99%
“…NKX2-5 is a transcription factor previously demonstrated to have highly specific expression in heart tissue, which is in congruence with the fact that this gene belongs to the top quantile (40) within both our specificity quantile and mean expression quantile metrics. This gene was in fact the first known genetic risk factor for congenital heart disease, and its expression is necessary not only for the development of cardiomyocytes but also the continued functioning of heart cells into adulthood 32,33 .…”
Section: Exemplar Results Identify Known Associations While Revealing...mentioning
confidence: 99%
“…Studies have shown a specific involvement in the development of the outflow tract and the right ventricle while also regulating the formation of the conduction system [52][53][54]. Approximately 2-4% of all CHDs can be associated with SNPs in the NKX2-5 gene [17], particularly linked with septal defects (ASDs and VSDs) or outflow tract defects (tetralogy of Fallot, double-outlet right ventricle, and transposition of the great arteries) [55,56]. CNVs involving this gene were also reported; one patient carrying a triplication of the 5q35.3 region, including the NKX2-5 gene, was found through MLPA screening of a CHD multicentric cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The nkx2.5 and sox9b genes play important regulatory roles in the differentiation of cardiac precursor cells, the circularization of the heart, the formation of the atrioventricular septum, and the maintenance of mature cardiac function [ 44 , 45 ]. We examined the mRNA levels of these genes and found that melatonin blunted the arsenite-induced low expression.…”
Section: Discussionmentioning
confidence: 99%